A Toolbox of Surgical Techniques for Palatal Fistula Repair. (February 2021) - Rothermel, Alexis T.; Lundberg, Jaclyn N.; Samson, Thomas D.; Tse, Raymond W.; Allori, Alexander C.; Bezuhly, Michael; Beals, Stephen P.; Sitzman, Thomas J.
Objective: To provide an inventory of oronasal fistula repair techniques alongside expert commentary on which techniques are appropriate for each fistula type. Design: A 4-stage approach was used to develop a consensus on surgical techniques available for fistula repair: (1) in-person discussion of oronasal fistula cases among cleft surgeons, (2) development of a schema for fistula management using transcripts of the in-person case discussion, (3) evaluation of the preliminary schema via a web-based survey of additional cleft surgeons, and (4) revision of the management schema using survey responses. Participants: Six cleft surgeons participated in the in-person case discussion. Eleven additional surgeons participated in the web-based survey. Participants had diverse training experiences, having completed residency and fellowship at 20 different hospitals. Results: A schema for fistula management was developed, organized by fistula location. The schema catalogues all viable approaches for each location. For fistulae involving the soft palate, the schema stresses the importance of evaluating for velopharyngeal insufficiency (VPI) and incorporating VPI management into fistula repair. For fistulae involving the hard palate, the schema separately enumerates the techniques available for nasal lining repair and for oral lining repair in each region. The schema also catalogues the diversity of approaches to lingual- and labioalveolar fistula, including variation in timing, orthodontic preparation, and simultaneous alveolar bone grafting. Conclusions: This study employed consensus methods to create a comprehensive inventory of available fistula repair techniques and to identify preferential techniques among a diverse group of surgeons.